What are the changes in LCA passengers' mobility practices? Insights from a European survey. (December 2021) - Craps, Amandine
Highlights: Investigate changes in mobility practices of LCAs' passengers. Broad understanding of what constitutes a practice, and the interactions between its numerous facets. Six-month survey with a large sample on past and present mobility practices. Links between travel frequency, length of stays, motives, travel party and accommodation. Changes in mobility practices, especially concerning VFR motives. Abstract: Low-cost airlines (LCAs) have been widely explored, but surprisingly, scholars have paid little attention to passengers' mobility practices and the changes that have occurred since LCAs' entry into the market. These practices were investigated through a large, in-depth survey amongst departing LCA passengers from Charleroi Airport, Belgium (N = 1471), conducted over six months to minimise seasonality issues. This study captures the profiles of LCA's passengers and travel practices before and after the entry of LCAs, with a focus on travel frequency, length of stays, travel motives, travel party and accommodation. This study finds that these elements of mobility practices are all closely interrelated and change through time. A new relation to time and space emerges and travel frequencies and length of stays appear to be less differentiated according travel motives. Thereby, very frequent and very short trips are not specific to business trips anymore and they spread to tourism and visiting friends and relative (VFR) motives. However, VFR related trips also show very long stays which balance the general decrease in length of stays. This specific travel motive has risen significantly over the years, inducing other changes such as an increased number of trips made alone and the choice of free accommodation like VFR or own housing contrary to business and tourism motives which remain in more mainstream accommodation choices and travel party. Additionally, it is not those who used to travel a lot by plane in the past who travel a lot with LCAs today. Thus, LCAs' passengers are either newly mobile or coming from other transport modes implying new or changed mobility practices.